Dimensions of Land Inequality and Economic Development - Erickson, Lennart; Vollrath, Dietrich (Washington, D.C. : International Monetary Fund, 2004)
There are several theories linking land inequality with aspects of economic development. Empirical work on these theories has attempted to establish a relationship between land inequality and institutions, financial development, and education. This research, though, has relied on measures of land inequality that capture only inequality within the class of landholders, ignoring completely the issue of landlessness. This omission raises suspicion about the usefulness of those empirical results. We use a new measure of the breadth of landholdings across the agricultural population to address this issue. We test the proposed relationships regarding land inequality and development using the new measure. The regressions fail to find significant and robust relationships between land inequality of either type and institutions or financial development. We do find that lower land inequality across agricultural populations, but not inequality within the landholding class, is associated with greater public provision of education.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet